If the numbers \[\left( {2n - 1} \right)\], \[\left( {3n + 2} \right)\] and \[\left( {6n - 1} \right)\] are in A.P., then find the value of n and the numbers.
Answer
Verified
442.8k+ views
Hint: This problem is from arithmetic progression. We are given three terms in the form of n and they are in A.P. so it is clear that there is a common difference d in two consecutive terms. So we will form two equations in n and d form. One equation from first and second term and the other is from first and third term. On solving them we will get the value of n and d. from that we will find the numbers. So let’s solve it!
Step by step solution:
Given that \[\left( {2n - 1} \right)\] , \[\left( {3n + 2} \right)\] and \[\left( {6n - 1} \right)\] are in A.P.
So let d be the common difference. Then we can write,
\[\left( {3n + 2} \right) - \left( {2n - 1} \right) = d\] ……..equation1
Now on solving the equation above we get,
\[ \Rightarrow 3n + 2 - 2n + 1 = d\]
Taking similar terms on one side we get,
\[ \Rightarrow 3n - 2n + 2 + 1 = d\]
\[ \Rightarrow n + 3 = d\] …….equation1.1
Now the difference in first and third term is 2d. then we can write,
\[\left( {6n - 1} \right) - \left( {2n - 1} \right) = 2d\] …….equation2
Now on solving the equation above we get,
\[ \Rightarrow 6n - 1 - 2n + 1 = 2d\]
Taking similar terms on one side we get,
\[ \Rightarrow 6n - 2n - 1 + 1 = 2d\]
\[ \Rightarrow 4n = 2d\]
So on further simplification,
\[ \Rightarrow n = \dfrac{d}{2}\]
\[d = 2n\]
This is the value of d.
From 1.1 we get \[ \Rightarrow d - n = 3\]
Putting the value of d in the equation above,
\[ \Rightarrow 2n - n = 3\]
\[ \Rightarrow n = 3\]
This is the value of n \[ \Rightarrow n = 3\] .
Now putting the value one by one in the numbers given we get the numbers also.
First number: \[\left( {2n - 1} \right) = 2 \times 3 - 1 = 6 - 1 = 5\]
Second number: \[\left( {3n + 2} \right) = 3 \times 3 + 2 = 9 + 2 = 11\]
Third number: \[\left( {6n - 1} \right) = 6 \times 3 - 1 = 18 - 1 = 17\]
Thus the numbers are \[5,11,17\].
Note:
Note that the numbers are given that they are already in A.P. so they have the relation in them. We can solve the problem by finding the value of common difference also. That is just need to find the first number and rest two can be found by adding the common difference. How? See below.
\[
\Rightarrow n + 3 = d \\
\Rightarrow d - n = 3 \\
\Rightarrow d - \dfrac{d}{2} = 3 \\
\Rightarrow \dfrac{d}{2} = 3 \\
\Rightarrow d = 3 \times 2 = 6 \\
\]
Now First number: \[\left( {2n - 1} \right) = 2 \times 3 - 1 = 6 - 1 = 5\]
Then second number \[5 + d = 5 + 6 = 11\]
Then third number \[11 + d = 11 + 6 = 17\]
Step by step solution:
Given that \[\left( {2n - 1} \right)\] , \[\left( {3n + 2} \right)\] and \[\left( {6n - 1} \right)\] are in A.P.
So let d be the common difference. Then we can write,
\[\left( {3n + 2} \right) - \left( {2n - 1} \right) = d\] ……..equation1
Now on solving the equation above we get,
\[ \Rightarrow 3n + 2 - 2n + 1 = d\]
Taking similar terms on one side we get,
\[ \Rightarrow 3n - 2n + 2 + 1 = d\]
\[ \Rightarrow n + 3 = d\] …….equation1.1
Now the difference in first and third term is 2d. then we can write,
\[\left( {6n - 1} \right) - \left( {2n - 1} \right) = 2d\] …….equation2
Now on solving the equation above we get,
\[ \Rightarrow 6n - 1 - 2n + 1 = 2d\]
Taking similar terms on one side we get,
\[ \Rightarrow 6n - 2n - 1 + 1 = 2d\]
\[ \Rightarrow 4n = 2d\]
So on further simplification,
\[ \Rightarrow n = \dfrac{d}{2}\]
\[d = 2n\]
This is the value of d.
From 1.1 we get \[ \Rightarrow d - n = 3\]
Putting the value of d in the equation above,
\[ \Rightarrow 2n - n = 3\]
\[ \Rightarrow n = 3\]
This is the value of n \[ \Rightarrow n = 3\] .
Now putting the value one by one in the numbers given we get the numbers also.
First number: \[\left( {2n - 1} \right) = 2 \times 3 - 1 = 6 - 1 = 5\]
Second number: \[\left( {3n + 2} \right) = 3 \times 3 + 2 = 9 + 2 = 11\]
Third number: \[\left( {6n - 1} \right) = 6 \times 3 - 1 = 18 - 1 = 17\]
Thus the numbers are \[5,11,17\].
Note:
Note that the numbers are given that they are already in A.P. so they have the relation in them. We can solve the problem by finding the value of common difference also. That is just need to find the first number and rest two can be found by adding the common difference. How? See below.
\[
\Rightarrow n + 3 = d \\
\Rightarrow d - n = 3 \\
\Rightarrow d - \dfrac{d}{2} = 3 \\
\Rightarrow \dfrac{d}{2} = 3 \\
\Rightarrow d = 3 \times 2 = 6 \\
\]
Now First number: \[\left( {2n - 1} \right) = 2 \times 3 - 1 = 6 - 1 = 5\]
Then second number \[5 + d = 5 + 6 = 11\]
Then third number \[11 + d = 11 + 6 = 17\]
Recently Updated Pages
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Statement I Reactivity of aluminium decreases when class 11 chemistry CBSE
Trending doubts
10 examples of friction in our daily life
The correct order of melting point of 14th group elements class 11 chemistry CBSE
Difference Between Prokaryotic Cells and Eukaryotic Cells
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
State and prove Bernoullis theorem class 11 physics CBSE
What organs are located on the left side of your body class 11 biology CBSE